تصور حقيقة الموازنات المقاصدية في الشرع - طالبي, عابد (University of Eloued جامعة الوادي, 2018)
لقد تقرر عند أهل العلم أن الحكم على الشيء فرع عن تصوره، وذلك أن الأحكام الصحيحة لا تكون في الغالب ‏إلا بعد المعرفة بحقيقة الشيء، ولما كان تصور الميزان المقاصدي مفترق طرق بين من عرفه على حقيقته فاهتدى، وبين ‏من وهِم وأخطأ القصد فَزَلّ وضلّ، كان من الضروري تنزيل ذلك المقرّر على ميزان المقاصد الشرعية لتصوره التصور ‏الصحيح، بالنظر في مواهي كل من الموازنة، والمقاصد، والشرع؛ بتتبع ذيولها في اللغة ومواردها في الشريعة وما اصطلح ‏عليه أهل كل فن؛ للوصول إلى التعريف المجمل الذي نلمس فيه تظاهر وتظافر تلك الحقائق في بيان المدلول الأوفى ‏والأمثل للميزان المرضي الصحيح.‏ ‏ ‏ ‏ ‏ perception of the fact of the finalities balancing in the islamic law. ‎ It is decided by the scholars that the Judging of the thing is a branch of his ‎visualization, A people differed in their perception of balancing to the purposes ‎of ‎Shari'ah between those who knew him, and then follow the path of truth; and between ‎those who erred in understanding; It was necessary to apply that decision on the ‎balance of legitimate goals to imagine the correct perception; Which requires ‎consideration of the definitions of the balancing; makassid; legitime; In terms of the ‎linguistic facts, and the idiom and legitimacy, to arrive at a comprehensive definition, ‎which we see the convergence of these facts in a statement to the correct balancing.‎‎
مقال بمجلة الشهاب
Keywords: الموازنة؛ المقاصد؛ الشرع؛ الحقائق؛ التقديم والاعتبار؛ التأخير أوالإهدار; the perception; the facts; the finalities; the balancing; the islamic law; the ‎waste; the consideration